Firms’ commitment to Halal standard practices in the food sector: impact of knowledge and attitude - Nurul Hudani Md Nawi; Puteri Hayati Megat Ahmad; Habibie Ibrahim (Emerald Group Publishing Limited, 2022)
The purpose of this study is to examine the effect of knowledge and attitude on firms’ commitment to Halal standard practices in a developing nation’s food sector. Additionally, the moderating effect of gender on this association is explored. The partial least squares-structural equation modelling (PLS-SEM) technique is used to analyse the results of a self-administered questionnaire completed by 200 internal Halal executive officers of multinational corporations and small and medium enterprises in a developing nation’s food sector. The empirical findings reflect the significant role of attitude in influencing firms’ commitment to Halal standard compliance in the food sector and thereby contribute towards improving organisational performance. In more detail, male respondents were more likely than female respondents to have a favourable attitude toward Halal standards in the food industry. Additionally, a positive attitude can influence how employees are judged on their adherence to Halal standard processes. This encouraging outcome is the result of joint efforts by all government agencies, statutory bodies and private organisations involved in Halal practices. Halal food producers should engender greater commitment to Halal standard practices within the buyer–supplier relationship due to the crucial nature of Halal concerns in food production. They should place a premium on strategic planning to safeguard the integrity of Halal food for consumption. This study considerably advances the existing body of knowledge by applying the consumer decision model to explain the relationships between knowledge, attitude and firms’ commitment to Halal standard practices in the food industry of a developing nation, with gender serving as a moderating variable. The empirical findings addressed the research gap by offering noteworthy insight into a subject that has received minimal attention in prior studies.